The Concept of Knowledge in the Qur'an: A Perspective from Majid Irsan al Kailany - Sumarno, Sumarno; Darmanto, Darmanto; Zanuba Alfin, Khusna (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2023)
This paper delves into the concept of knowledge as portrayed in the Quran, utilizing the perspective of Majid Irsan al Kailany, a renowned Islamic scholar known for his profound works in philosophy and Islamic education. The primary objective is to elucidate the Quranic viewpoint on knowledge, its purpose, sources, and implications, as interpreted by Majid Irsan al Kailany. The study employs a qualitative approach, analyzing relevant Quranic verses and interpreting them through the lens of Majid Irsan al Kailany's scholarly works, particularly his treatise on Islamic philosophy and education. The analysis involves identifying key themes related to knowledge, exploring their significance, and understanding their implications in the context of Islamic teachings. The analysis reveals several key findings. Firstly, the Quran underscores the importance of knowledge as a means to draw closer to Allah, emphasizing its spiritual dimension. Secondly, the Quran is depicted as a comprehensive source of knowledge encompassing various aspects of life and the universe, beyond mere moral guidance. Thirdly, belief in Allah and the Quran is highlighted as a fundamental prerequisite for the pursuit and acquisition of knowledge. Lastly, a profound understanding and practical application of Quranic teachings are deemed essential in obtaining beneficial knowledge. The study concludes that according to Majid Irsan al Kailany's perspective, the Quran promotes knowledge as a spiritual endeavor to understand the greatness of Allah and His creation. It emphasizes the Quran's role as a multifaceted source of knowledge and underscores the importance of belief, deep understanding, and practical application of its teachings in acquiring beneficial knowledge for human life.